The Investigation of Metallic Silver Dissolution Kinetics Using DL-Malic Acid with Hydrogen Peroxide Solution as an Eco-Friendly Leaching System: The Rotating Disc Method - Motasim, Mahmoud; Boyrazli, Mustafa; Aydogan, Salih; Agacayak, Tevfik; Ali, Babiker (Springer, 2025)
Although cyanidation remains widely employed for silver recovery due to its cost-effectiveness, it presents serious environmental and health hazards. In this study, the dissolution kinetics of silver were investigated in an environmentally benign leaching system composed of DL-malic acid and hydrogen peroxide, employing the rotating disc method. High-purity silver discs (99.99 pct) were used to examine the effects of rotation speed, disc surface area, temperature, and the concentrations of DL-malic acid and hydrogen peroxide on the leaching rate. X-ray diffraction (XRD) and Fourier-transform infrared spectroscopy (FTIR) were conducted to characterize the silver surface before and after leaching. Additionally, contact angle measurements were performed to evaluate the interfacial interaction between the leaching solution and the silver surface. The results demonstrated that the dissolution rate increased with temperature, rotation speed, hydrogen peroxide concentration, and surface area. However, elevated concentrations of DL-malic acid resulted in the formation of a passivating layer on the silver surface, likely due to chelation effects, which significantly impeded the access of protons (H+) to the silver surface, thereby reducing the dissolution rate. Contact angle analysis further indicated reduced wettability at higher DL-malic acid concentrations, with values reaching up to 87.80 deg. XRD analysis confirmed the partial oxidation of the silver surface, forming Ag2O. The reaction was determined to be chemically controlled, with an activation energy of 44.14 kJ/mol.
Keywords: Citric-Acid; Cyanidation; Gold; Recovery; Concentrate; Behavior; Thiourea; Lithium; Oxidant; Alloys